Decomposition of Ilmenite in Hydrochloric Acid to Obtain High Grade Titanium Dioxide - Wahyuningsih, Sayekti; Pramono, Edi; Firdiyono, Florentinus; Sulistiyono, Eko; Budi Rahardjo, Sentot; Hidayattullah, Hari; A. Anatolia, Fauchi (Asian Journal of Chemistry, 2013)
Ilmenite is an economically important and interesting mineral. It is found as a by-product of tin mining in Bangka Indonesia. This mineral can be used as the source of making titanium metal, titanium dioxide (TiO2) pigment and material for dye sensitized solar cell. The aim of this research is to investigate the possibility of using Bangka ilmenite mineral to obtain TiO2 pigments solar cell grade. The main feature of the process is the use of Fe0 as reducing agent to reduces iron value in ilmenite to acid leachingable form. In order to obtain high grade TiO2, ilmenite was oxidized and leached with a hydrochloric acid solution at several conditions. Oxidation was performed at temperatures of 400, 500, 600, 700, 800, 900, 100 and 1100 ºC without and with Na2S addition. Several parameters of leaching such as iron particles addition and hydrochloric acid concentration were evaluated. Ilmenite without oxidation was also leached for comparison. Original ilmenite and solid products of both oxidation and leaching were characterized by X-ray diffraction and X-ray fluorescence, whereas solutions obtained after leaching were analyzed by atomic absorption and UV-VIS spectrophotometry for iron and titanium determination, respectively. It was established that pre-oxidation contributes with iron dissolution due to the iron diffusion that occur during that process. However for iron dissolution is crucial the presence of iron particles as they reduce the ferric iron obtained after oxidation. The temperature of oxidation has an effect on type, proportion and distribution of phases. Pseudobrookite and randomly distributed rutile are obtained at higher temperatures and they showed great crystallinity and grade of product, nevertheless the presence of pseudobrookite promotes titanium dissolution.